“The resource-based paradigm – a special emphasis on work- force capital as a competitive strategy in businesses” - Parameswaran, Hima (Advances in Social Sciences Research Journal, 2020)
It is a known fact that organizational strategies have created a competitive advantage of organizations. However, this competitiveness can be achieved only with the proper deployment of human, physical, and organizational resources. A study on the resource-based paradigm, specifically on human assets, explores the significance of human involvement and human investment perspective in enterprises. In view of that, a mixed approach, with a quantitative and qualitative survey was conducted in randomly selected manufacture industries in the UAE. The statistical analysis, with the help of SPSS 20 confirms the correlation between this model with its latent variables, talent management and change management, towards a strategic move. Moreover, the results prove that this RBV can enhance the mobility of various resources in the organization, maintain a culture, uphold gain-sharing, and boost network opportunities for the organizational and individual competencies.